Cardiovascular Biomechanics - Hoskins, Peter R.; Lawford, Patricia V.; Doyle, Barry J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a balanced presentation of the fundamental principles of cardiovascular biomechanics research, as well as its valuable clinical applications. Pursuing an integrated approach at the interface of the life sciences, physics and engineering, it also includes extensive images to explain the concepts discussed. Cardiovascular biomechanics encompasses the relationship between the mechanics of the cardiovascular system and biological function in health and disease, and it is increasingly recognised that normal function and diseases involve a complex interplay between biology and mechanical forces. With a focus on explaining the underlying principles, this book examines the physiology and mechanics of circulation, mechanobiology and the biomechanics of different components of the cardiovascular system, in-vivo techniques, in-vitro techniques, and the medical applications of this research. Written for undergraduate and postgraduate students and including sample problems at the end of each chapter, this interdisciplinary text provides an essential introduction to the topic. It is also an ideal reference text for researchers and clinical practitioners, and will benefit a wide range of students and researchers including engineers, physicists, biologists and clinicians who are interested in the area of cardiovascular biomechanics.
Introduction to fluid and solid mechanics -- Introduction to biomechanics of the cardiovascular system -- Blood and blood flow -- Arterial biomechanics I. Pressure, flow and stiffness -- Arterial biomechanics II. Forces, adaptability and mechanotransduction -- Excitation-contraction in the heart -- Biomechanics of the venous system -- Biomechanics of the microcirculation -- Medical imaging -- Modelling of the cardiovascular system -- Patient specific modelling -- Flow phantoms -- Measurement of the mechanical properties of biological tissues -- Hypertension -- Atherosclerosis -- Aneurysms -- Cardiovascular prostheses -- Appendix 1: Questions -- Appendix 2: Glossary -- Index.
Keywords: Medicine; Human physiology; Cardiology; Medical physics; Radiation; Biomedical engineering; Medicine & Public Health; Cardiology; Biomedical engineering; Medical and Radiation Physics; Human physiology